Political competition and the allocation of public investment in Mexico - Eduardo Rodriguez-Oreggia; Joan Costa-Font; Dario Luna Pla (European Regional Science Association (ERSA), 2002)
This paper examines the causality between central government spending in regions and local elections, in an environment of increasing electoral competition and a undefined decentralisation. This study examines Mexican elections during the period 1990-1995 where the main party started loosing part of its influence and there were many claims of use of the budget to favour the central governing party. We employ data on public investment and municipalities ruled by the PRI in each Mexican region. The evidence shows that there is opportunistic behaviour of the central government using public investment to gain local control of pressures for decentralisation.
Keywords: 330